Pesque-e-solte, uma alternativa para conservação de recursos pesqueiros?: Avaliação da atividade em Salminus brasiliensis - Sanches, Ricardo Augusto Kuche (2015)
The development and improvement of management techniques are fundamental to conserve the biodiversity of freshwater ecosystems. Recreational fishing through catch-and-release, can be used to assist management actions that seek to promote the sustainable use of fisheries resources by the reduction fishing mortality. However, this practice can cause damage to captured and released individuals, requiring that minimal mortality occurs without significant injuries to the catch-and-release be considered efficient and thus, it may be used as a tool of fishery management. For this reason it is necessary the realization of specific researches for each fish species, geographic region, applied handling and equipment used. In search of an additional alternative of management for the conservation of fish stocks and with the assumption that the use of catch-and-release be a measure applicable as a tool of management, the present study had as objective experimentally evaluate the efficiency of catch and release in Salminus brasiliensis. To this end, the mortality and the difference in growth relative to different air exposure times were evaluated, determining a safe limit that may be implemented in practice. Therefore, it was used 287 individuals of S. brasiliensis identified by implanted microchips, that were stored in a farming tank and were submitted to activity of catch-and-release. This way, it was determined that the critical time for handling the specie after capture was 546 s, from that time the probability of death is higher than 5%. Furthermore, it was observed that there were no significant changes in organic growth in caught and released individuals. Thus, the catch-and-release can be considered effective as a tool to assist the management and conservation of this specie if it is conducted properly. Additionally, it was proposed the insertion of the catch-and-release in the control of fishing, alternatives to its use, monitoring, supervision and research.